Eficacia del sistema de alerta temprana “Emilia” en los años 2023 y 2024: análisis desde un enfoque de competencias - Dávila López, Dayanara Polette (2025)
This research addresses the study of the effectiveness of the “Emilia” Early Warning System in Ecuador during the years 2023 and 2024, focused on the implementation and analysis of the competencies of the institutions in charge of activating and monitoring it. This system is established as a crucial mechanism for the protection of missing children and adolescents (NNA), which is why we sought to identify the factors that affect its effectiveness. This research was developed with a non-experimental field design and a qualitative approach. Interviews were conducted with representatives of the institutions responsible for activating the alert, in order to understand their capacity to respond to the alert and evaluate their effectiveness in situations of disappearances. In addition, emblematic cases of disappearances of children and adolescents were analyzed, such as those of Génesis and Briana Campo and Dana Ramos, based on information provided by public media. The results reveal that the Early Warning System presents significant flaws in the coordination and performance of the institutions, which affects the speed and effectiveness of locating missing minors. Omissions in inter-institutional communication and lack of training of key personnel for search and location were identified. It is concluded that there is a need to improve training and inter-institutional coordination, and it is recommended to review the action protocols to guarantee a more efficient response in accordance with the best interests of the child, always seeking the protection and well-being of children and adolescents in risk situations.